Chemotherapy administration-related adverse events and their impact on patient management: the case of Rituximab - DAOUDI, Hajar; EL MARNISSI, Safaa; BOUSLIMAN, Yassir; SERRAGUI, Samira; AIT EL CADI, Mina (Jour Med Resh and Health Sci, 2023)
Introduction: Rituximab is a monoclonal antibody that targets CD20 and is indicated for the treatment of certain autoimmune diseases and some types of blood cancer such as non-Hodgkin's lymphoma and chronic lymphocytic leukaemia. Rituximab may also cause side effects. Some of the possible side effects include allergic reactions, infections, infusion-related reactions and skin reactions. The aim of this study is to evaluate the efficacy and safety of rituximab administration. Materials & methods: This is a retrospective descriptive study conducted at the pharmacovigilance unit of the pharmacy of Ibn Sina Rabat hospital from January 2017 to December 2022 on the cases of adverse reactions notified to the hospital, whose aim is to identify the causality of the adverse reaction that occurred following the administration of Rituximab using the French imputability method Results & discussion: The number of reported cases of adverse events related to the administration of Rituximab in the context of chemotherapy reported by the haematology oncology department is 17. Mild adverse events constituted 29.4% and 70.6% of the cases required prolongation of hospitalisation with increased medical follow-up. Following the numerous reports of rituximab infusion, the risk minimisation action opted for by the pharmacist was to adjust the infusion rate, starting with an infusion rate of 50mg/hr for 30 minutes, then increasing by 50mg/hr every 30 minutes up to a maximum of 400mg/hr. Conclusion: This study illustrates the importance of the role of the pharmacist in detecting pharmacovigilance alerts, as well as raising the awareness of nurses and physicians to the risks of administering drugs that can cause angioedema, in particular rituximab. In order to prevent and reduce the risk of incidence and improve vital prognosis.